Improvement of Literacy and Numeracy Abilities with Calistung Learning Using Card Media - Prodyanatasari, Arshy (S&Co Publishing, 2024)
SDN Blimbing is one of the primary schools in Blimbing village, Mojo sub-district, Kediri district. 90.90% of grade 1 students at SDN Blimbing experience difficulties in learning to read, write and count (Calistung). Low Calistung skills will reduce students' literacy and numeracy skills. To overcome this, it is necessary to provide Calistung learning program assistance to each student individually based on the level of difficulty and student needs. The type of research conducted is descriptive qualitative with Participatory Action and Learning (PALS) research and the learning strategy applied is collaborative learning, where the fun learning strategy is collaborated with the individual system and individualized educational program (IEP). This research activity was conducted through 4 stages: (1) Initial Data Collection, (2) Advocacy, (3) Assistance, and (4) Monitoring and evaluation. Based on the descriptive analysis conducted, it was found that the Calistung learning assistance program can improve the literacy and numeracy skills of grade 1 students of SDN Blimbing 1, Kediri District.